A method for preparing polycarbonate / ramie fiber composite material

Through the combination of modified corchobic fibers and polycarbonate, composite materials with high antibody cracked ability and good processing performance are prepared, and the problems of insufficient performance and poor environmental protection in existing technologies have been solved.

CN118515960BActive Publication Date: 2025-01-24东莞市丰龙新材料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410803822.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-01-24
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

The impact resistance and stress cracking resistance of existing polycarbonate/glass fiber composites are insufficient, and synthetic fibers are expensive, have large energy consumption and are not environmentally friendly.

Method used

Use the styrene-Malay anhydride-acryline hyper-supported symbolic polymer modifiers of ramie fiber, prepare polycarbonate/radon fiber composite materials through double screw extrusion technology, improve the interface compatibility of fiber and polycarbonate Processing performance.

Benefits of technology

The stress cracking resistance of the polycarbonate/ramie fiber composite material is significantly improved, its processing performance is improved, and the production cost is reduced. The material is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118515960B_ABST
    Figure CN118515960B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fiber-reinforced polymer composite materials, and specifically relates to a method for preparing a polycarbonate / ramie fiber composite material, synthesizing a styrene-acrylonitrile-maleic anhydride hyperbranched copolymer, mixing 60-85 parts by weight of polycarbonate, 10-30 parts by weight of ramie fiber and 5-10 parts by weight of the hyperbranched copolymer, and then adding the mixture into a hopper, and preparing the polycarbonate / ramie fiber composite material with a twin-screw extruder. In the present invention, the crosslinking degree of the hyperbranched polymer and the ratio of various structural units are adjustable, and the compatibility of polycarbonate and ramie fiber can be effectively enhanced; the ramie fiber treated with dilute alkali solution has good performance and is green and environmentally friendly; a general twin-screw extruder can be used to prepare the polycarbonate / ramie fiber composite material by blending polycarbonate with ramie fiber and hyperbranched copolymer, and no equipment investment needs to be increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fiber-reinforced polymer composite materials, and particularly relates to a method for preparing a polycarbonate / ramie fiber composite material. Background Art

[0002] Polycarbonate (PC) is a commonly used engineering plastic with the characteristics of thermal stability, weather resistance, creep resistance, impact resistance, and high mechanical strength. It is widely used in electrical appliances, automobiles, sports equipment, packaging and other fields. However, PC also has disadvantages, such as high processing temperature (250 oC-300 oC), poor fluidity, easy stress cracking, and sensitivity to notches. Fiber reinforcement can significantly improve the fatigue resistance, wear resistance and stress cracking resistance of PC, and can reduce the water absorption, molding shrinkage and cost of PC. It is a commonly used PC modification method (S. Kore, VSMD Murthy, N. Hiremath, M. Theodore, S. Young, D.Penumadu, U. Vaidya.Textile-grade carbon fiber-reinforced polycarbonate composites: effect of epoxy sizing.Ind. Eng. Chem. Res., 2021, 60, 3981−3991). At present, commonly used reinforcing fibers mainly include glass fiber, carbon fiber, aramid fiber, etc. (YM Ghazzawi, AF Osorio, MT Heitzmann. Fire performance of continuous glass fiber reinforced polycarbonate composites: the effect of fiber architecture on the fire properties of polycarbonate composites. J Compos. Mater., 2019, 53, 1705-1715). However, the interface compatibility between glass fiber and PC is not ideal, and the impact resistance and stress cracking resistance of the composite material need to be improved urgently. In addition, except for glass fiber, the above synthetic fibers are expensive, require a lot of energy in the production process, and are not environmentally friendly. If they are not properly recycled, their widespread use will lead to serious ecological problems.

[0003] Natural fibers are obtained from animals and plants, have excellent biodegradability, and cause almost no environmental pollution when used. At present, many natural fibers, such as flax, hemp, jute and sisal fibers, have been widely used in the research of reinforced and toughened plastics (V. Chauhan, T. Kärki, J. Varis. Review of natural fiber reinforced engineering plastic composites, their applications in the transportation sector and processing techniques. J Thermoplast. Compos., 2022, 35, 1169-1209). The density of natural fibers (1.2-1.6 g / cm3) is about half the density of glass fibers (2.2-2.7 g / cm3), which can greatly reduce the mass of composite materials. In addition, the energy consumed in the production of natural fibers is about 80% less than that consumed in the production of glass fibers, which greatly saves energy. Therefore, the use of natural fibers to reinforce and toughen polymer materials has gained increasing attention in academia and industry. Among many natural fibers, ramie fiber has a high cellulose content and is the only ramie fiber that can be spun in a single fiber state, making it the veritable "king of natural fibers". However, ramie fiber has a high water content and poor compatibility with PC, and untreated ramie fiber will partially thermally degrade in the polycarbonate processing temperature range. Therefore, there is no precedent for the application of natural ramie fiber to directly reinforce and toughen polycarbonate. The present invention intends to prepare a high-performance polycarbonate / natural fiber composite material by synthesizing a hyperbranched polymer modified ramie fiber that is resistant to high temperatures and has good compatibility with polycarbonate. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a polycarbonate / ramie fiber composite material in view of the deficiencies in the prior art, wherein a styrene-maleic anhydride-acrylonitrile hyperbranched copolymer is synthesized as a reinforcing agent. Under the twin-screw extrusion temperature condition, the maleic anhydride group can react with the hydroxyl group on the surface of the ramie fiber to improve the interfacial bonding strength between the ramie fiber and the polycarbonate. In addition, the hyperbranched structure molecules have the characteristics of being difficult to entangle between molecules and having low viscosity, which effectively improves the processing performance of the polycarbonate / ramie fiber composite material. The polycarbonate / ramie fiber composite material in the present invention can be prepared using a conventional twin-screw extruder without increasing the equipment investment cost.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] The method for preparing the polycarbonate / ramie fiber composite material provided by the present invention comprises the following specific steps:

[0007] (1) Styrene (St), maleic anhydride (MAH), acrylonitrile (AN) and 1,4-divinylbenzene (DVB) are added to a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel, and then the initiator AIBN is dissolved in a small amount of St and added in batches, and the temperature is raised to carry out a polymerization reaction. After a period of reaction, the reaction liquid becomes viscous, and the reactant is taken out, cooled to become a solid, and crushed with a pulverizer to obtain an irregular granular hyperbranched copolymer;

[0008] (2) Soak the ramie fiber in a sodium hydroxide solution for a period of time, rinse it with tap water, dry it in a vacuum oven, and then cut it into short fibers;

[0009] (3) Polycarbonate (PC), ramie fiber and hyperbranched copolymer are mixed and placed in a hopper of a twin-screw extruder, and a polycarbonate / ramie fiber composite material is obtained after melt extrusion.

[0010] In step (1), the mass ratio of St: MAH: AN: DVB is 10: (5-10): (5-10): (0.5-2), the amount of AIBN is (0.2-2)% of the total mass of the monomers, the reaction temperature is 65-75 °C, and the reaction time is 15-30 h;

[0011] In step (2), the original diameter of the ramie fiber is 15-70 μm, the moisture content after drying is no more than 0.1%, the concentration of sodium hydroxide is (1-2) wt%, the temperature of the vacuum oven is set to 85-95 °C, and the length of the short fiber is 2-10 mm;

[0012] In step (3), the polycarbonate is a commercially available bisphenol A type, has a molecular weight of (2-5)×104 g / mol, a density of 1.18-1.25 g / cm3, and a water absorption rate after drying of no more than 0.025%. The mass ratio of PC to ramie fiber and hyperbranched copolymer is: (60-85): (10-30): (5-10). The temperature ranges of the barrel, screw and die of the screw extruder are: (250-260 oC), (265-280 oC), (265-275 oC), respectively, and the screw speed is 150-300 rmp / min.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] (1) The synthesized styrene-maleic anhydride-acrylonitrile hyperbranched copolymer can not only improve the interfacial force between ramie fiber and polycarbonate through the anhydride group, but also improve the melt flow properties of the composite material due to its special hyperbranched structure, improve its processing ability, and can be injection molded into thin-walled devices.

[0015] (2) Ramie fiber is a natural fiber with strong environmental protection properties.

[0016] (3) The preparation process is simple, no organic solvent is required, and no waste liquid or waste gas is generated. Conventional twin-screw extruders can be used without increasing equipment investment costs.

[0017] (4) The stress cracking resistance of polycarbonate / ramie fiber composite materials is greatly improved, and injection molded products do not crack. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of preparation of the composite material of the present invention;

[0019] Figure 2 is the infrared spectrum of the styrene-maleic anhydride-acrylonitrile hyperbranched copolymer in Example 1 of the present invention;

[0020] Figure 3 The H-NMR spectrum of the styrene-maleic anhydride-acrylonitrile hyperbranched copolymer in Example 1;

[0021] Figure 4 Gel permeation chromatography characterization results of the styrene-maleic anhydride-acrylonitrile hyperbranched copolymer in Example 1. DETAILED DESCRIPTION

[0022] A method for preparing a polycarbonate / ramie fiber composite material comprises the following specific steps:

[0023] (1) Styrene (St), maleic anhydride (MAH), acrylonitrile (AN) and 1,4-divinylbenzene (DVB) are added to a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel, and then the initiator AIBN is dissolved in a small amount of St and added in batches, and the temperature is raised to carry out a polymerization reaction. After a period of reaction, the reaction liquid becomes viscous, and the reactant is taken out, cooled to become a solid, and crushed with a pulverizer to obtain an irregular granular hyperbranched copolymer;

[0024] (2) Soak the ramie fiber in a sodium hydroxide solution for a period of time, rinse it with tap water, dry it in a vacuum oven, and then cut it into short fibers;

[0025] (3) mixing polycarbonate (PC), ramie fiber and hyperbranched copolymer and placing them into a hopper of a twin-screw extruder, and obtaining a polycarbonate / ramie fiber composite material after melt extrusion;

[0026] In step (1), the mass ratio of St: MAH: AN: DVB is 10: (5-10): (5-10): (0.5-2), the amount of AIBN is (0.2-2)% of the total mass of the monomers, the reaction temperature is 65-75 °C, and the reaction time is 15-30 h;

[0027] In step (2), the original diameter of the ramie fiber is 15-70 μm, the moisture content after drying is no more than 0.1%, the concentration of sodium hydroxide is (1-2) wt%, the temperature of the vacuum oven is set to 85-95 °C, and the length of the short fiber is 2-10 mm;

[0028] In step (3), PC is commercially available bisphenol A type, with a molecular weight of (2-5)×104 g / mol, a density of 1.18-1.25 g / cm3, and a water absorption rate after drying of no more than 0.025%. The mass ratio of PC to ramie fiber and hyperbranched copolymer is: (60-85): (10-30): (5-10). The temperature ranges of the barrel, screw and die of the screw extruder are: (250-260 oC), (265-280 oC), (265-275 oC), respectively, and the screw speed is 150-300 rmp / min.

[0029] The present invention is further described below through specific implementation examples. Example

[0030] (1) St, MAH, AN and DVB were added into a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel in a mass ratio of 10:5:5:2. AIBN was weighed according to 1% of the total mass of the monomers and dissolved with 1 part of St. Nitrogen was blown into the reaction liquid at a rate of 10 mL / min for 0.5 h, the reaction temperature was raised to 70oC, AIBN was added in 5 times with a time interval of 1 h. After a reaction period of 20 h, the reaction liquid became viscous. The reactants were taken out and cooled to become solids. They were crushed with a pulverizer to obtain irregular granular hyperbranched copolymers;

[0031] (2) Soak the ramie fiber in a 2 wt% sodium hydroxide solution for a period of time, rinse it with tap water for 5 times, dry it in a 90°C vacuum oven, and then cut it into 3-5 mm short fibers;

[0032] (3) Polycarbonate, ramie fiber and hyperbranched copolymer were mixed in a mass ratio of 60:30:10 and placed in the feeding hopper of a twin-screw extruder. The temperature ranges of the barrel, screw and die of the twin-screw extruder were 260 oC, 275 oC and 270 oC, respectively. The screw speed was 260 rmp / min. After melt extrusion, granulation was performed to obtain a polycarbonate / ramie fiber composite material. Example

[0033] (1) St, MAH, AN and DVB were added into a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel in a mass ratio of 10:5:5:2. AIBN was weighed according to 1% of the total mass of the monomers and dissolved with 1 part of St. Nitrogen was bubbled into the reaction liquid at a rate of 10 mL / min for 0.5 h. The reaction temperature was raised to 70°C. AIBN was added in 5 times with a time interval of 1 h. After a reaction time of 20 h, the reaction liquid became viscous. The reactants were taken out and cooled to become solids. They were crushed with a pulverizer to obtain irregular granular hyperbranched copolymers.

[0034] (2) Soak the ramie fiber in a 2 wt% sodium hydroxide solution for a period of time, rinse it with tap water for 5 times, dry it in a 90°C vacuum oven, and then cut it into 3-5 mm short fibers;

[0035] (3) Polycarbonate, ramie fiber and hyperbranched copolymer were mixed in a mass ratio of 70:20:10 and placed in the feeding hopper of a twin-screw extruder. The temperature ranges of the barrel, screw and head of the twin-screw extruder were 260 oC, 275 oC and 270oC, respectively. The screw speed was 260 rmp / min. After melt extrusion, granulation was performed to obtain a polycarbonate / ramie fiber composite material. Example

[0036] (1) St, MAH, AN and DVB were added into a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel in a mass ratio of 10:5:5:2. AIBN was weighed according to 1% of the total mass of the monomers and dissolved with 1 part of St. Nitrogen was bubbled into the reaction liquid at a rate of 10 mL / min for 0.5 h. The reaction temperature was raised to 70°C. AIBN was added in 5 times with a time interval of 1 h. After a reaction time of 20 h, the reaction liquid became viscous. The reactants were taken out and cooled to become solids. They were crushed with a pulverizer to obtain irregular granular hyperbranched copolymers.

[0037] (2) Soak the ramie fiber in a 2 wt% sodium hydroxide solution for a period of time, rinse it with tap water for 5 times, dry it in a 90°C vacuum oven, and then cut it into 3-5 mm short fibers;

[0038] (3) Polycarbonate, ramie fiber and hyperbranched copolymer were mixed in a mass ratio of 80:10:10 and placed in the feeding hopper of a twin-screw extruder. The temperature ranges of the barrel, screw and head of the twin-screw extruder were 260 oC, 275 oC and 270 oC, respectively. The screw speed was 260 rmp / min. After melt extrusion, granulation was performed to obtain a polycarbonate / ramie fiber composite material. Example

[0039] (1) St, MAH, AN and DVB were added into a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel in a mass ratio of 10:5:5:0.5, and AIBN was weighed according to 1% of the total mass of the monomers and dissolved with 1 part of St. Nitrogen was bubbled into the reaction liquid at a rate of 10 mL / min for 0.5 h, the reaction temperature was raised to 70oC, and AIBN was added in 5 times with a time interval of 1 h. After a reaction period of 20 h, the reaction liquid became viscous, and the reactant was taken out and cooled to become a solid, which was crushed with a pulverizer to obtain irregular granular hyperbranched copolymers;

[0040] (2) Soak the ramie fiber in a 2 wt% sodium hydroxide solution for a period of time, rinse it with tap water for 5 times, dry it in a 90°C vacuum oven, and then cut it into 3-5 mm short fibers;

[0041] (3) Polycarbonate, ramie fiber and hyperbranched copolymer were mixed in a mass ratio of 60:30:10 and placed in the feeding hopper of a twin-screw extruder. The temperature ranges of the barrel, screw and die of the twin-screw extruder were 260 oC, 275 oC and 270 oC, respectively. The screw speed was 260 rmp / min. After melt extrusion, granulation was performed to obtain a polycarbonate / ramie fiber composite material. Example

[0042] (1) St, MAH, AN and DVB were added into a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel in a mass ratio of 10:5:5:0.5. AIBN was weighed according to 1% of the total mass of the monomers and dissolved with 1 part of St. Nitrogen was bubbled into the reaction liquid at a rate of 10 mL / min for 0.5 h. The reaction temperature was raised to 70°C. AIBN was added in 5 times with a time interval of 1 h. After a reaction time of 20 h, the reaction liquid became viscous. The reactants were taken out and cooled to become solids. They were crushed with a pulverizer to obtain irregular granular hyperbranched copolymers.

[0043] (2) Soak the ramie fiber in a 2 wt% sodium hydroxide solution for a period of time, rinse it with tap water for 5 times, dry it in a 90°C vacuum oven, and then cut it into 3-5 mm short fibers;

[0044] (3) PC, ramie fiber and hyperbranched copolymer were mixed in a mass ratio of 70:20:10 and placed in the hopper of a twin-screw extruder. The temperature ranges of the barrel, screw and die of the twin-screw extruder were 260 oC, 275 oC and 270 oC, respectively. The screw speed was 260 rmp / min. After melt extrusion, granulation was performed to obtain a polycarbonate / ramie fiber composite material. Example

[0045] (1) St, MAH, AN and DVB were added into a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel in a mass ratio of 10:5:5:0.5. AIBN was weighed according to 1% of the total mass of the monomers and dissolved with 1 part of St. Nitrogen was bubbled into the reaction liquid at a rate of 10 mL / min for 0.5 h. The reaction temperature was raised to 70°C. AIBN was added in 5 times with a time interval of 1 h. After a reaction time of 20 h, the reaction liquid became viscous. The reactants were taken out and cooled to become solids. They were crushed with a pulverizer to obtain irregular granular hyperbranched copolymers.

[0046] (2) Soak the ramie fiber in a 2 wt% sodium hydroxide solution for a period of time, rinse it with tap water for 5 times, dry it in a 90°C vacuum oven, and then cut it into 3-5 mm short fibers;

[0047] (3) Polycarbonate, ramie fiber and hyperbranched copolymer were mixed in a mass ratio of 80:10:10 and placed in the feeding hopper of a twin-screw extruder. The temperature ranges of the barrel, screw and head of the twin-screw extruder were 260 oC, 275 oC and 270 oC, respectively. The screw speed was 260 rmp / min. After melt extrusion, granulation was performed to obtain a polycarbonate / ramie fiber composite material. Example

[0048] (1) St, MAH, AN and DVB were added into a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel in a mass ratio of 10:1:9:2. AIBN was weighed according to 1% of the total mass of the monomers and dissolved with 1 part of St. Nitrogen was bubbled into the reaction liquid at a rate of 10 mL / min for 0.5 h. The reaction temperature was raised to 70°C. AIBN was added in 5 times with a time interval of 1 h. After a reaction time of 20 h, the reaction liquid became viscous. The reactants were taken out and cooled to become solids. They were crushed with a pulverizer to obtain irregular granular hyperbranched copolymers.

[0049] (2) Soak the ramie fiber in a 2 wt% sodium hydroxide solution for a period of time, rinse it with tap water for 5 times, dry it in a 90°C vacuum oven, and then cut it into 3-5 mm short fibers;

[0050] (3) PC, ramie fiber and hyperbranched copolymer were mixed in a mass ratio of 60:30:10 and placed in the feeding hopper of a twin-screw extruder. The temperature ranges of the barrel, screw and die of the twin-screw extruder were 260 oC, 275 oC and 270 oC, respectively. The screw speed was 260 rmp / min. After melt extrusion, granulation was performed to obtain a polycarbonate / ramie fiber composite material. Example

[0051] (1) St, MAH, AN and DVB were added into a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel in a mass ratio of 10:1:9:2. AIBN was weighed according to 1% of the total mass of the monomers and dissolved with 1 part of St. Nitrogen was bubbled into the reaction liquid at a rate of 10 mL / min for 0.5 h. The reaction temperature was raised to 70°C. AIBN was added in 5 times with a time interval of 1 h. After a reaction time of 20 h, the reaction liquid became viscous. The reactants were taken out and cooled to become solids. They were crushed with a pulverizer to obtain irregular granular hyperbranched copolymers.

[0052] (2) Soak the ramie fiber in a 2 wt% sodium hydroxide solution for a period of time, rinse it with tap water for 5 times, dry it in a 90°C vacuum oven, and then cut it into 3-5 mm short fibers;

[0053] (3) Polycarbonate, ramie fiber and hyperbranched copolymer were mixed in a mass ratio of 70:20:10 and placed in the feeding hopper of a twin-screw extruder. The temperature ranges of the barrel, screw and head of the twin-screw extruder were 260 oC, 275 oC and 270oC, respectively. The screw speed was 260 rmp / min. After melt extrusion, granulation was performed to obtain a polycarbonate / ramie fiber composite material. Example

[0054] (1) St, MAH, AN and DVB were added into a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel in a mass ratio of 10:1:9:2. AIBN was weighed according to 1% of the total mass of the monomers and dissolved with 1 part of St. Nitrogen was bubbled into the reaction liquid at a rate of 10 mL / min for 0.5 h. The reaction temperature was raised to 70°C. AIBN was added in 5 times with a time interval of 1 h. After a reaction time of 20 h, the reaction liquid became viscous. The reactants were taken out and cooled to become solids. They were crushed with a pulverizer to obtain irregular granular hyperbranched copolymers.

[0055] (2) Soak the ramie fiber in a 2 wt% sodium hydroxide solution for a period of time, rinse it with tap water for 5 times, dry it in a 90°C vacuum oven, and then cut it into 3-5 mm short fibers;

[0056] (3) Polycarbonate, ramie fiber and hyperbranched copolymer were mixed in a mass ratio of 80:10:10 and placed in the feeding hopper of a twin-screw extruder. The temperature ranges of the barrel, screw and head of the twin-screw extruder were 260 oC, 275 oC and 270 oC, respectively. The screw speed was 260 rmp / min. After melt extrusion, granulation was performed to obtain a polycarbonate / ramie fiber composite material.

[0057] Sample testing method prepared by the present invention:

[0058] (1) The infrared test of hyperbranched polymers was carried out in the following manner:

[0059] The instrument was a Nicolet 6700 in ATR mode with a test range of 4000-400 cm-1.

[0060] (2) The molecular weight test of hyperbranched polymer is carried out in the following manner:

[0061] The mobile phase was DMF, two Agilent columns (Polar Gel-M and Polar Gel-L), the eluent flow rate was 1.0 mL / min, the column temperature was 50 °C, and the column standard curve was calibrated with polystyrene to determine the relative molecular weight (Mn).

[0062] (3) The properties of polycarbonate / ramie fiber composites were evaluated as follows:

[0063] The tensile test was carried out using a universal material testing machine in accordance with ASTM D638 standard, with a tensile speed of 50mm / min. The bending test was carried out using a universal material testing machine in accordance with ASTM D790 standard. The notched impact specimens were prepared in accordance with GB / T1843 and tested using a cantilever beam impact tester in accordance with ASTM D-256 standard. The melt flow rate of the dried polycarbonate / ramie fiber composite material was measured at 300°C on a melt flow rate meter in accordance with GB / T3682-2000 standard. Each group of specimens was tested 5 times and the average value was taken. The polycarbonate / ramie fiber composite material was injection molded, and a circular hole with a diameter of 6mm was designed for the injection part. The injection part was soaked in glacial acetic acid for 10 seconds to observe whether cracks appeared near the circular hole.

[0064] Figure 2The peak at 3028 cm-1 is the stretching vibration peak of the unsaturated CH bond on the benzene ring, the peak at 2926 cm-1 is the characteristic absorption peak of the CH of the polystyrene chain segment, the peaks at 758 cm-1 and 702 cm-1 are the bending vibration absorption peaks of the CH of the benzene ring, the peaks at 1605 cm-1, 1456 cm-1, and 1495 cm-1 are the vibration absorption peaks of the C=C bond of the benzene ring, the peak at 2239 cm-1 is the characteristic absorption peak of the cyano group (-CN), the peak at 1079 cm-1 is the stretching vibration absorption peak of the C-CN bond, the peaks at 1778 cm-1 and 1855 cm-1 are the characteristic absorption peaks of the symmetrical and asymmetrical stretching vibration of the carbonyl group in maleic anhydride, and the peak at 1226 cm-1 is the stretching vibration characteristic absorption peak of COC in the cyclic anhydride. This shows that styrene, maleic anhydride, and acrylonitrile all participated in the polymerization to form a styrene-maleic anhydride-acrylonitrile copolymer.

[0065] Figure 3 It is the nuclear magnetic hydrogen spectrum of the styrene-maleic anhydride-acrylonitrile hyperbranched copolymer in Example 1. Among them, the signal peak of the benzene ring hydrogen in the styrene structural unit appears at 6.5-7.5 ppm, the signal peak of the maleic anhydride structural unit hydrogen appears at 3.2-3.6 ppm, the signal peak of the methine hydrogen in the styrene and acrylonitrile structural units appears at 2.0-2.3 ppm, and the signal peak of the styrene and acrylonitrile methylene hydrogen appears at 1.2-2.0 ppm, which proves that the styrene-maleic anhydride-acrylonitrile copolymer has been synthesized.

[0066] Figure 4 The gel permeation chromatography characterization results of the styrene-maleic anhydride-acrylonitrile hyperbranched copolymer in Example 1. As can be seen from the figure, the number average molecular weight of the hyperbranched polymer is 63.1×103, which is far greater than the molecular weights of styrene (104.15), maleic anhydride (98.06) and acrylonitrile (53.06) monomers, indicating that the polymerization reaction has successfully occurred. In addition, the gel permeation chromatography curve of the polymer is multimodal, and the molecular weight distribution is as high as 4.11, which is consistent with the molecular weight distribution characteristics of hyperbranched polymers.

[0067] The main properties of the polycarbonate / ramie fiber composite material prepared according to the above example are shown in the following table:

[0068] Tensile strength(MPa) Elongation at break (%) Bending strength(MPa) Flexural modulus (MPa) <![CDATA[Notched impact strength (kJ / m 2 )]]> Melt index (g / 10 min) Cracking glacial acetic acid (10 s) Polycarbonate 55.9 71 85.1 2360 51 6.6 Cracking Example 1 Sample 65.1 28 109.5 3536 60 8.5 No cracking Example 2 Sample 71.6 30 121.6 3921 65 11.3 No cracking Example 3 Sample 64.3 43 106.5 3433 56 7.7 No cracking Example 4 Sample 63.3 29 99.6 3126 57 7.3 No cracking Example 5 Sample 69.9 31 109.3 3522 61 8.6 No cracking Example 6 Sample 61.3 46 93.1 2983 54 7.0 No cracking Example 7 Sample 59.1 33 93.9 2985 55 8.3 No cracking Example 8 Sample 65.1 35 101.6 3310 59 11.1 No cracking Example 9 Sample 58.3 49 91.5 2913 53 7.9 No cracking

[0069] The above description is only a preferred embodiment of the present invention, so all equivalent changes or modifications made according to the structure, characteristics and principles described in the scope of the patent application of the present invention are included in the scope of the patent application of the present invention.

Claims

1. A method for preparing a polycarbonate / ramie fiber composite material, characterized in that: The specific steps include: (1) Styrene (St), maleic anhydride (MAH), acrylonitrile (AN) and 1,4-divinylbenzene (DVB) are added to a four-necked flask equipped with a reflux condenser, a thermometer, a mechanical stirrer and a constant pressure dropping funnel, and then the initiator AIBN is dissolved in a small amount of St and added in batches, and the temperature is raised to carry out a polymerization reaction. After a period of reaction, the reaction liquid becomes viscous, and the reactant is taken out, cooled to become a solid, and crushed with a pulverizer to obtain an irregular granular hyperbranched copolymer; (2) Soak the ramie fiber in a sodium hydroxide solution for a period of time, rinse it with tap water, dry it in a vacuum oven, and then cut it into short fibers; (3) mixing polycarbonate, ramie fiber and hyperbranched copolymer and placing them into a hopper of a twin-screw extruder, and obtaining a polycarbonate / ramie fiber composite material after melt extrusion; In step (1), the mass ratio of St: MAH: AN: DVB is 10: (5-10): (5-10): (0.5-2), the amount of AIBN is (0.2-2)% of the total mass of monomers St, MAH, AN and DVB, the reaction temperature is 65-75 ° C, and the reaction time is 15-30 h; In step (2), the original diameter of the ramie fiber is 15-70 μm, the moisture content after drying is no more than 0.1%, the concentration of sodium hydroxide is (1-2) wt%, the temperature of the vacuum oven is set to 85-95° C., and the length of the short fiber is 2-10 mm; In step (3), PC is commercially available bisphenol A type, has a molecular weight of (2-5)×104 g / mol, a density of 1.18-1.25 g / cm3, and a water absorption rate after drying of no more than 0.025%. The mass ratio of PC to ramie fiber and hyperbranched copolymer is: (60-85): (10-30): (5-10). The temperature ranges of the barrel, screw and die of the screw extruder are: (250-260°C), (265-280°C), (265-275°C), respectively. The screw speed is 150-300 rmp / min.

Citation Information

Patent Citations

  • Polycarbonate / natural fiber composite material and preparation method thereof

    CN103788617A

  • Polycarbonate heat-conducting composite material and preparation method thereof

    CN104559109A